Socialetikken og det grundtvigske - Mortensen, Viggo (Grundtvig-Studier, 1985)
Social Ethics and the Grundtvigian Element Vartov Book 1984 Reviewed by Viggo Mortensen The reviewer is surprised to find in this book the related problems that he knows about from the area of ethics concerned with inter-personal relationships in institutions and societies. But he adds that grundtvigianism has made a crucial contribution to the restructuring of our society, also in an ethical direction. Grundtvigianism, however, was linked politically to liberalism, which often leaves moral principles and norms hanging in mid-air. The reviewer therefore regards the newly-aroused interest in narrative as valuable, for “the moral is found in the myth”, and there are both good and less good examples of this in the yearbook. There is high praise for Finn Jacobi’s brilliant article, “Can History Replace Myth?”, a question which he himself answers in the negative. Instead myth has been repressed, and now exercises its influence from undercover. The reviewer likewise commends the article “On Children with Behavioural Disorders” by Harald Rasmussen, a school psychiatrist, for its socio-ethical content. A further article in this area, by Dr Svend Andersen, is concerned with biotechnology and human worth. Naturally Grundtvig would never have used the word “socio-ethical”, but the idea was nonetheless part of his thought and is absolutely indispensable now.